Annals of Borno - University of Maiduguri ([Maiduguri, Nigeria] : The University, 1985)
In this volume, the natural sciences predominate with thirteen contributions in the areas of Agriculture (especially soil and crop sciences, as well as Agricultural economics), Geology, Geography, Ecology and Botany; while Human Sciences are represented by nine offerings in History, Ethnography, law, Sociology and Linguistics
Vol.II
osc 11/06/2019
Arch
Keywords: Yearbook; Borno State (Nigeria); Nigeria